IMPLEMENTASI KEBIJAKAN PEMBERIAN BANTUAN DANA HIBAH KEAGAMAAN DI KOTA TANGERANG (Studi Bagian Kesejahteraan Rakyat Sekretariat Daerah Kota Tangerang) - Juhri Juhri; Dafyar Eliadi H; Edi Mulyadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
The purpose of this study is to analyze the implementation of the religious grant policy organized by the People's Welfare Section of the Regional Secretariat of Tangerang City. The provision of religious grants in Tangerang City aims to support the achievement of goals, programs, activities, and sub-activities of the Regional government in accordance with the Regional interest in supporting the implementation of government, development, and community functions by taking into account the principles of justice, appropriateness, rationality, and benefits for the community. The grant policy implementation model approach in this study uses the concept of policy implementation from George Edward regarding the determinants of successful policy implementation, namely policy communication, policy resources, disposition and bureaucratic structure. The qualitative research method was used to describe the implementation of the grant policy organized by the People's Welfare Section of the Tangerang City Regional Secretariat by using analytical techniques through the data collection process of observation, interviews and observation which then conducted data reduction, data display and verification of conclusions through triangulation techniques. The research findings provide information that the implementation of the grant policy has been carried out well, although optimization efforts are needed regarding policy communication, policy resources, policy disposition and bureaucratic structure policy. Implementation of the grant policy requires coordination and communication that is carried out continuously and continuously. One of the coordination and communication media that can be used is by conducting socialization during pre-disbursement of religious grants, during grant disbursement and post-disbursement of grants. So that the use and management of grant aid received by religious organizations can be controlled, monitored and evaluated by the People's Welfare Section of the Tangerang City Regional Secretariat. Keywords: Policy Implementation, Religious Grants.